Meningkatkan Kemampuan Motorik Halus Anak Melalui Montessori Practical Life Kegiatan Water Pouring Anak Usia 4-5 Tahun Di TK Belby Bintaro - Christie, Gloria Agatha; Mulyanti, Fitrah; Hatiningsih, Nuligar (Neolectura, 2025)
This study aims to improve the fine motor skills of children aged 4-5 years through water pouring activities in Class A of Belby Bintaro Kindergarten, involving 10 children in the 2024/2025 academic year. This research is a Classroom Action Research (CAR) using the Kemmis and Taggart model. The implementation was carried out in two cycles. The data collection techniques used include observation, documentation, and field notes, which were then analyzed qualitatively and quantitatively. According to Arikunto’s theory and research data, the fine motor skill level before the intervention was 10%, then increased to 30% in Cycle I, and showed a significant improvement in Cycle II, reaching 77.5%. The results of this study reinforce that Montessori practical life activities, specifically water pouring, are one of the factors that can enhance young children’s fine motor skills..